ANALISIS KESALAHAN BERBAHASA DI BIDANG DIKSI DALAM BUKU PANDUAN UPT PERPUSTAKAAN IAIN SURAKARTA EDISI 2018 - Nurul Fajriyani; Mochammad Rosyid Ridho; Qoriatul Laili (Jurnal Penelitian Humaniora, 2020)
The library guide book certainly has a significant role in the learning process for new students. All forms of direction contained in this book are important to consider in terms of language. This study aimed to describe language errors in diction and spelling found in the guide book. The purpose of this study was to describe language errors in the diction and spelling. The research method used was descriptive qualitative, using error analysis framework. Data collection technique was done qualitatively. The data analysis was done in the following stages: processing and preparing data to be analyzed, reading and describing the entire data, recording all data obtained, analyzing more details and describing errors in each data, classifying each data in spelling or diction fields, and interpreting all data according to relevant. The results of the analysis indicated that there were 25 errors on diction, consisting of 3 prepositional writing errors, 17 standard word writing errors, and 5 italics writing data. In addition, there were 10 errors the spelling field, consisting of 2 data on punctuation, and 8 errors in the use of foreign words.